2013
DOI: 10.1177/1538192713513463
|View full text |Cite
|
Sign up to set email alerts
|

Early Coursework and College Experience Predictors of Persistence at a Hispanic-Serving Institution

Abstract: Utilizing survival analysis, we examined two key first year courses, mathematics and English, and tested whether they were predictive for long-term student success as measured by persistence to graduation at a Hispanic-serving research university. While first math and first English courses were significant, SAT score was not for Hispanic and Black students. High school grade point average (GPA) was significant for Hispanic students but not for White or Black students. ResumenUtilizando el análisis de supervive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The findings revealed a strong association between higher GPA and financial aid; that is, students who received higher dollar amounts of need-based grants earned high grades (Tuttle & Musoba, 2013). Similar effects were observed in the studies of Musoba and Krichevskiy (2014) and R. Chen (2012). According to R. Chen (2012), needsbased financial aid packages substantially boost retention for low-income students and work to narrow the socioeconomic graduation gap.…”
Section: Community College Transfer Studentssupporting
confidence: 52%
See 3 more Smart Citations
“…The findings revealed a strong association between higher GPA and financial aid; that is, students who received higher dollar amounts of need-based grants earned high grades (Tuttle & Musoba, 2013). Similar effects were observed in the studies of Musoba and Krichevskiy (2014) and R. Chen (2012). According to R. Chen (2012), needsbased financial aid packages substantially boost retention for low-income students and work to narrow the socioeconomic graduation gap.…”
Section: Community College Transfer Studentssupporting
confidence: 52%
“…Different patterns emerged for the associations of academic indicators to persistence and graduation for students of the three ethnic groups (Musoba & Krichevskiy, 2014). With respect to academic preparation, high school GPA emerged as a significant factor in graduation for Latino students but not for White or Black students and composite SAT had no significant impact on persistence or graduation for students of any ethnicity.…”
Section: Academic Readiness and Retentionmentioning
confidence: 89%
See 2 more Smart Citations
“…HSIs are more likely to be the first in their families to attend college, be first-or secondgeneration immigrants, attend college part-time, work off-campus, and be academically underprepared for college (ASHE, 2013;Cuellar, 2014Cuellar, , 2015de los Santos & Cuamea, 2010). In general, at HSIs, the academic attainment of Latina/o students is not predicted by standardized test scores (Musoba & Krichevskiy, 2014;Vaquera & Maestas, 2009). In a result similar to that of students at non-HSIs, research has indicated that at HSIs the positive interaction between Latina/o students and faculty increases their academic performance (DeFreitas & Bravo, 2012).…”
Section: Hispanic Serving Institutionsmentioning
confidence: 99%